Physicians' attitude toward the withdrawal of life-sustaining treatment: A comparison between Korea, Japan, and China. Issue 10 (25th November 2016) - Ryu, Ji Yeong; Bae, Hyuna; Kenji, Hattori; Xiaomei, Zhai; Kwon, Ivo; Ahn, Kyong Jin
ABSTRACT: End-of-life care decision making has become a matter of serious ethical and legal concern in the three Far East Asian Countries of China, Japan, and Korea. Researchers in the three countries collaboratively conducted a comparative descriptive study with respect to physicians' perspectives concerning end-of-life care decisions. In spite of cultural similarities, each country has its own unique set of social, cultural, and political circumstances. So the content and scope of policies and laws on end-of-life decision reflect the differing views of people based on their social status, moral values, religious beliefs, and economic status.